2015
DOI: 10.4236/ojped.2015.54049
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Severely Malnourished Children Aged 6 - 59 Months on Outpatient Management Program in Kitui County Hospital, Kenya

Abstract: Background: Severe acute malnutrition is a widely prevalent problem in developing countries and a major cause of morbidity and mortality. Traditionally, children with severe acute malnutrition were rehabilitated within inpatient services. Advent of ready to use therapeutic food made it possible to treat majority of these children in their homes. However, there is limited data about the outcomes of the program. Objectives: To determine the outcomes (recovery, default, mean weight gain and non-response rates) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
4
12
1
Order By: Relevance
“…Also, this finding was comparable with a study conducted among children treated at OTP in Wolaita zone (4.2 g/kg/day) [21]. This finding was slightly lower than the study conducted in Kenya (5.1 g/kg/day), Kamba district (5.76 g/kg/day) and Shebedino district (5.4 g/kg/day) [4,20,22]. The possible reasons for the low weight gain might be associated with late detection of children with SAM that would increase the risk of co-morbidities which in turn would have resulted in the weight gain falling short of the standard.…”
Section: Plos Onesupporting
confidence: 85%
See 2 more Smart Citations
“…Also, this finding was comparable with a study conducted among children treated at OTP in Wolaita zone (4.2 g/kg/day) [21]. This finding was slightly lower than the study conducted in Kenya (5.1 g/kg/day), Kamba district (5.76 g/kg/day) and Shebedino district (5.4 g/kg/day) [4,20,22]. The possible reasons for the low weight gain might be associated with late detection of children with SAM that would increase the risk of co-morbidities which in turn would have resulted in the weight gain falling short of the standard.…”
Section: Plos Onesupporting
confidence: 85%
“…The disparities in recovery time might be attributable to differences in treatment and caring practices among facilities since most of the previous studies were conducted on data from hospitals, health centers and health posts [22,25] and this study assessed the recovery at health post level. Besides this, the difference might be due to differences in adherence to guidelines to optimal management of children under OTP across regions [4], differences in seasons and setting-specific differences in predictors of time-torecovery in the different contexts of the studies. The finding might particularly indicate that HEWs at health posts in the periphery of the health care system are able to provide management of SAM at OTPs to the national recommended standards set for median recovery time though efforts are needed to shorten the time-to-recovery to the global standards.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…4 These results provide notice that the recovery rate of children with acute severe malnutrition is still low, therefore an intervention program is needed to improve welfare and health of the child in the future. 14 The differences in recovery outcomes may be influenced by socioeconomic status, quality of treatment, clean and healthy life behavior, access to supplementary food and health services, and finally the difference in malnutrition management guidelines in each area. The study in Africa conducted by Grebemichael et al 10 shows similar results.…”
Section: Discussionmentioning
confidence: 99%
“…The study reported that socio-demographic factors such as age and residence are not associated with recovery rates, however immunization status is proportionally correlated with severe acute malnutrition in children. 14 Furthermore, pneumonia occurred in 35% of SAM patients, pneumonia is the most frequent comorbid disease suffered by the subjects. The incidence of pneumonia is still high in Indonesia, data from a study conducted by Rudan et al in Tan 15 also showed that in Surabaya and Denpasar are 283 cases/100,000 children and 347 cases/100,000 children.…”
Section: Discussionmentioning
confidence: 99%